Genome Sequencing of Pleurozium schreberi: The Assembled and Annotated Draft Genome of a Pleurocarpous Feather Moss. Issue 9 (1st September 2019) - Pederson, Eric R A; Warshan, Denis; Rasmussen, Ulla
Abstract: The pleurocarpous feather moss Pleurozium schreberi is a ubiquitous moss species which plays a fundamental role in many terrestrial ecosystems, for instance within the boreal forest, the Earth's largest terrestrial biome, this species plays a significant role in driving ecosystem nitrogen and carbon inputs and fluxes. By hosting dinitrogen (N2 )-fixing cyanobacteria, the moss-cyanobacteria symbiosis constitutes the main nitrogen input into the ecosystem and by the high productivity and the low decomposability of the moss litter, P . schreberi contributes significantly to build-up soil organic matter, and therefore long-term C sequestration. Knowledge on P. schreberi genome will facilitate the development of 'omics' and system's biology approaches to gain a more complete understanding of the physiology and ecological adaptation of the moss and the mechanisms underpinning the establishment of the symbiosis. Here we present the de novo assembly and annotation of P. schreberi genome that will help investigating these questions. The sequencing was performed using the HiSeq X platform with Illumina paired-end and mate-pair libraries prepared with CTAB extracted DNA. In total, the assembled genome was approximately 318 Mb, while repetitive elements account for 28.42% of the genome and 15, 992 protein-coding genes were predicted from the genome, of which 84.23% have been functionally annotated. We anticipate that the genomic data generated will constitute a significant resource to study ecological and evolutionary genomics of P. schreberi, and will be valuable for evo-devo investigations as well as our understanding of the evolution of land plants by providing the genome of a pleurocarpous moss.